Sharecropping and the Interlinking of Agrarian Markets - Stiglitz, Joseph E.; Braverman, Avishay (American Economic Review, 1982)
In this article the authors present a general set of arguments applicable to both competitive and noncompetitive environments, to situations where all the terms of the contract are determined in an optimal way, as well as to situations where many of the terms are specified institutionally. Much of the formal analysis of this article focuses on showing how the landlord, by altering, say, the terms at which he makes loans available to his tenants, not only can induce the tenant to borrow more but, more importantly, can induce the tenant to work harder or to undertake projects which are more to the liking of the landlord. Section I of this article examines interlinked credit and tenancy contracts; section II examines interlinked marketing and tenancy contracts; section III points out the possible interlinking between labor contracts and consumption goods markets; and section IV presents the different equilibrium frameworks discussed in this article, that is, monopoly, monopsony, competition, and equilibria with surplus labor.